Clinicoepidemiological profile and outcome in patients of covid 19 with normal chest x-ray: study of 51 patients - Firdaus, Huma; Khan, Nafees Ahmad; Reza, Maqsumi; Khan, Mansoor Ahmad; Krishnan, Gishnu; Razak, Nader Abdul; Verma, Arushi; Shameem, Mohammad; Bhargava, Rakesh (International Journal of Research in Medical Sciences, 2020)
Background: Covid 19 was declared a pandemic by WHO on 11 March 2020. Patients usually have pneumonia on chest x-ray at time of presentation however many patients also do not develop pneumonia and have normal chest x-ray. Methods: A total of 51 patients above the age of 15 years diagnosed with covid 19 by RT PCR of nasopharngeal/oropharyngeal samples were included in the study. History of symptoms onset was recorded, chest x-ray and haematological investigations were done of all patients. Results: A total of 51 patients >15 years of age were included in the study. 28 were male and 23 were female patients. Maximum number of patients were in age group 15-30 years. Most common presenting complain was fever (49% patients). Most common comorbidity was diabetes mellitus. There was no mortality reported in patients with normal chest x-ray. Conclusions: We conclude from the current study that patients with normal chest x-ray at the time of presentation have a very good outcome.